On the full Kostant-Toda system and the discrete Korteweg-de Vries equations - Barrios Rolanía, Dolores (2015)
The relation between the solutions of the full Kostant–Toda lattice and the discrete Korteweg–de Vries equation is analyzed. A method for constructing solutions of these systems is given. As a consequence of the matricial interpretation of this method, the transform of Darboux is extended for general Hessenberg banded matrices.